2010
DOI: 10.1161/hypertensionaha.109.146282
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Mediates Endothelial Adaptations to Exercise Training in Humans

Abstract: Abstract-Although episodic changes in shear stress have been proposed as the mechanism responsible for the effects of exercise training on the vasculature, this hypothesis has not been directly addressed in humans. We examined brachial artery flow-mediated dilation, an index of NO-mediated endothelial function, in healthy men in response to an acute bout of handgrip exercise and across an 8-week period of bilateral handgrip training. Shear stress responses were attenuated in one arm by cuff inflation to 60 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
358
6
32

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 398 publications
(423 citation statements)
references
References 40 publications
27
358
6
32
Order By: Relevance
“…In keeping with previous studies in healthy young volunteers, exercise training lead to a rapid functional increase in both groups. Whilst continued exercise training has been associated with normalisation of endothelial function after 6-8 weeks in young healthy subjects (Tinken et al 2008;Tinken et al 2010;Birk et al 2012), we observed preservation of the increase in brachial artery endothelial function after 6-8 weeks in both groups in this study. This suggests the presence of a distinct time-course in vascular adaptations to exercise training in middle-aged type 2 diabetes patients and older subjects, compared with young healthy individuals.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In keeping with previous studies in healthy young volunteers, exercise training lead to a rapid functional increase in both groups. Whilst continued exercise training has been associated with normalisation of endothelial function after 6-8 weeks in young healthy subjects (Tinken et al 2008;Tinken et al 2010;Birk et al 2012), we observed preservation of the increase in brachial artery endothelial function after 6-8 weeks in both groups in this study. This suggests the presence of a distinct time-course in vascular adaptations to exercise training in middle-aged type 2 diabetes patients and older subjects, compared with young healthy individuals.…”
Section: Discussioncontrasting
confidence: 39%
“…cycling/running exercise) (Birk et al 2012;Tinken et al 2008) or small muscle group (i.e. handgrip exercise) (Tinken et al 2010) training in healthy young volunteers have consistently demonstrated that 2 weeks of exercise training is sufficient to significantly enhance vascular function. This initial rapid increase in vascular function is often normalised after 6-8 weeks of training.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies provide strong evidence that (repeated) elevations in antegrade or mean SR represent a potent hemodynamic stimulus that acutely and chronically alters vascular function and structure 1, 5, 6, 7, 8, 9, 10. As a logical follow‐up study from initial findings that acute elevation in retrograde shear induces impairment in endothelial function,2 this study aimed to assess the effect of chronic (ie, 2 weeks) manipulation of retrograde SR in humans in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, shear stress follows a cyclic pattern, directed towards the periphery during systole (antegrade shear) and, under some circumstances, directed backwards to the heart during diastole (retrograde shear) 4. Elevations in antegrade shear stress are associated with potentially beneficial effects on the vessel wall 1, 5, 6, 7, 8, 9, 10. In contrast, elevation in retrograde shear stress may be potentially detrimental 2, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation